Dietary lecithin improves feed efficiency without impacting meat quality in immunocastrated male pigs and gilts fed a summer ration containing added fat - Akit, Henny; Collins, Cherie; Fahri, Fahri T.; Hung, Alex; D'Souza, Darryl; Leury, Brian; Dunshea, Frank (Elsevier, 2018)
The aim of this study was to investigate the effects of sex and dietary lecithin on growth performance, meat quality, muscle collagen content and gene expression of key genes involved in collagen synthesis in finisher pigs. A total of 256 pigs (Large White × Landrace) were allotted to a 2 × 2 factorial arrangement involving sex (gilt or immunocastrated [IC] male) and dietary treatment (0 or 5 g/kg of dietary lecithin). All diets were formulated to contain 4.6% tallow with relatively high total fat of 6.3%. After 5 weeks of dietary treatment, pigs were slaughtered and Longissimus dorsi muscle was obtained for evaluation of meat quality and collagen content. Rectus abdominis muscle was analysed for gene expression of key genes involved in collagen synthesis namely, type I (α1) procollagen (COL1A1), type III (α1) procollagen (COL3A1), α-subunit of prolyl 4-hydroxylase (P4H), lysyl oxidase and metalloproteinase-1 (MMP-1). The results showed that lecithin improved feed efficiency of all pigs (P < 0.05) but it had no effect on feed intake, average daily gain and dressing percentage (P > 0.05). Lecithin also had no effect on meat compression, shear force, collagen content and gene expression (P > 0.05). Immunocastrated male had higher growth rate and increased COL1A1 expression than gilts. However, sex had no effect on fat depth at the P2 site (65 mm from the midline over the last rib), collagen content and expression of other genes (P > 0.05). In conclusion, lecithin improved feed efficiency in finishing pigs without impacting pork quality. Thus, inclusion of lecithin in diets containing high amount of tallow during the summer period could be beneficial.